How Many Cancer Clinical Trials Can a Clinical Research Coordinator Manage? The Clinical Research Coordinator Workload Assessment Tool. Issue 1 (16th January 2021) - Fabbri, Francesca; Gentili, Giorgia; Serra, Patrizia; Vertogen, Bernadette; Andreis, Daniele; Dall'Agata, Monia; Fabbri, Greta; Gallà, Valentina; Massa, Ilaria; Montanari, Emanuela; Monti, Manuela; Pagan, Flavia; et al.
Abstract : PURPOSE: Cancer clinical trials (CTs) are now more complex than ever before and require dedicated personnel (clinical research coordinators [CRCs]) to perform regulatory and administrative activities and protocol- and patient-related procedures. We developed a simple tool to measure the workload (WL) of CRCs involved in cancer research and to estimate personnel requirements within a Clinical Trial Center. METHODS: A literature review and 2-month period in which CRCs recorded their activities in a diary provided valuable information that led to the Istituto Scientifico Romagnolo per lo Studio e la Cura dei Tumori Workload Assessment Tool (IWAT) being divided into three sections: Protocol, On-Treatment Patients, and Follow-Up Patients. Twelve full-time senior CRCs from three sites of the Network measured their monthly WL for 30 months to evaluate IWAT reproducibility and accuracy. RESULTS: The IWAT proved to be a user-friendly tool (3-6 minutes required for each CT), with high reproducibility (interobserver reproducibility ranged from 82% to 100% for each IWAT item). In December 2017, the Network had 185 ongoing CTs, with a median of 2.5 active centers for each CT. On the basis of 448 total IWAT measures by CRCs, the majority of trials were academic (57%) or dealt with advanced disease (77%). The median IWAT WL score for each study was 20.98 ± 22.90 (range, 2-188) and 475 ± 229 (range, 150 [junior staff] - 930 [extreme heavy WL]) for each CRC. On the basis of our experience, a monthly WL score of 500-600 was considered an appropriate value for a full-time CRC. CONCLUSION: The IWAT could prove useful in evaluating CT complexity, estimating appropriate CRC WLs, and defining personnel requirements. Independent validation by other CRCs working in different organizational contexts and in different countries is needed.